Multiplex PCR Respiratory Panel in Indonesia: A Literature Review - Johan Nathan; Fariz Nurwidya; Anis Karuniawati (Respiratory Science, 2026)
Acute Respiratory Infections (ARIs) are a major cause of morbidity and mortality globally, especially among children under five years and elderly populations. Clinical symptoms-based diagnosis of ARI often fails to differentiate viral and bacterial etiologies, resulting in inappropriate antibiotic use or delayed antiviral administration. Conventional diagnostic methods such as culture and antigen detection have limitations in speed and accuracy. Multiplex PCR respiratory panels give a solution through simultaneous detection of various ARI-causing pathogens from a single clinical specimen. These panels demonstrate 30-50% higher sensitivity compared to conventional methods with the capability to identify up to 26 pathogen targets with significantly shorter turnaround times. This results in reduced hospitalization duration and optimized antimicrobial stewardship. Various commercial platforms are available in Indonesia with different characteristics, performance metrics, and pathogen coverage. Despite demonstrating significant advantages, these panels have limitations including inability to differentiate active pathogens from non-viable pathogens or colonization, high cost, and incomplete pathogen coverage. Optimal implementation requires appropriate clinical context consideration to maximize diagnostic benefit while minimizing risks of overdiagnosis and overtreatment.